The Effect of the Problem-Based Learning Model Based on Ethnomathematics on Students' Learning Outcomes as Seen in the Face of Learning Styles - M. Ramadhan Evendi; Aswar Anas; Dimas Anditha Cahyo Sujiwo (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the effect of the ethnomathematics-based Problem Based Learning (PBL) learning model on students' mathematics learning outcomes in terms of learning styles. The study used a quantitative approach with a quasi-experimental design. The subjects were 60 seventh-grade students of MTs Negeri 10 Jember who were divided into two groups, namely the experimental class and the control class. The experimental class received learning using the ethnomathematics-based PBL model, while the control class received conventional learning. The research instruments included a learning outcome test and a learning style questionnaire. Data analysis was carried out using a t-test (independent sample t-test) to determine differences in learning outcomes between the two groups. The results of the normality test showed that the data were normally distributed (p 0.05), and the homogeneity test showed that the data variance was homogeneous (p 0.05). The results of the t-test showed that there was a significant difference between the experimental class and the control class (p = 0.000 0.05). The average learning outcomes of students in the experimental class were higher. It can be concluded that the ethnomathematics-based PBL model is effective in improving mathematics learning outcomes, especially for students with a visual learning style.